Pengaruh Lingkungan Kerja, Kompetensi Dan Displin Kerja Terhadap Kinerja Pegawai Dengan Budaya Organisasi Sebagai Variabel Intervening Di Kantor Kecamatan Lamposi Tigo Nagori Kota Payakumbuh - Wengky Deumanutu (Jurnal Visi Manajemen, 2019)
Human resources who work in organizations should have the ability to improve the quality of performance. Many things affect the performance of employees in an agency including work ability, work environment, workload, competence, how the organizational culture of the agency and employee work discipline in carrying out their activities while in an agency, especially the Office of Lamposi Tigo Nagori District Payakumbuh City. This type of research is quantitative. The population in this study included the State Civil Apparatus (ASN) Lamposi Tigo Nagori District Office Payakumbuh City, amounting to 44 people. Data management in this study will use the smartPLS software. The environment, discipline and organizational culture do not significantly influence performance. Competence has a significant effect on performance. T count was obtained for 2.891 with a p value of 0.004. The work environment, competence and work discipline do not have a significant effect on performance after intervening variables of organizational culture. The high performance demands on Lamposi Tigo Nagori Sub-district Office employees in Payakumbuh City must be balanced with better provisioning of competencies through various trainings as well as more appropriate and appropriate rewards.